Pengaruh Kepemimpinan, Komitmen Organisasi dan Lingkungan Kerja terhadap Prestasi Kerja melalui Kepuasan Kerja Karyawan Sebagai Variabel Intervening Pada PT. KSK Insurance Indonesia - Ratlan Pardede (Universitas Bunda Mulia, 2016)
This study aims to determine the influenceof leadership, organizational commitment, working environment towardemployeeperformance through working satisfaction as intervening variable. This research was conducted at PT KSK Insurance Indonesia by using total sample of 180 employees. Structural Equation Modeling (SEM) by AMOS program version 22 used to test the hypothesis. The study concludes : (1)leadership has positive effect but not significant on working satisfaction, (2)commitment has positive and significant effect on working satisfaction, (3)working environment has positive and significant effect on working satisfaction, (4)leadership has positive effect but not significant on employee performance, (5)commitment has positive and significant effect on employeeperformance, (6)working environment has positive and significant effect on workingperformance, (7)working satisfaction has positive and significant effecton employeeperformance;Key Words: Leadership, organizational commitment, working environment, working satisfaction and employee performance.